Biochemical Evaluation of Silver Nanoparticles in Wistar Rats. (30th October 2014) - Adeyemi, Oluyomi Stephen; Adewumi, Ifeoluwa
Abstract : Background . Silver nanoparticles have found wider and increasing biomedical applications due to their broad antimicrobial characteristics. However, toxicity of nanoparticles is a subject of continued controversy, thus necessitating further studies in this direction. Objectives . This study investigated the biochemical effects of silver nanoparticles in Wistar rats. Materials and Methods . Forty male rats were randomly distributed into eight experimental groups of five. Group A served as the control and received distilled water. Groups B to H were orally exposed to varying concentrations of silver nanoparticles (AgNPs) at 100, 1000, and 5000 mg/kg daily for 7, 14, and 21 days alternately. Following cessation of treatments, rats were sacrificed and the blood and other vital organs were collected and prepared as specimens for biochemical analysis. Results . Administration of AgNPs to rats did not produce significant loss in feed intake and body weight. However, rat exposure to AgNPs caused significant alterations to levels of serum and tissue AST, ALT, and ALP. At the 100 mg/kg AgNPs exposure, rat serum and tissue AST and ALT levels were significantly decreased ( P < 0.05). In contrast, AgNPs administration elevated ( P < 0.05) ALP levels in rat serum and tissues. Conclusion . We show evidence that AgNPs administration to Wistar rats altered some biochemical parameters.